Analysis of Understanding and Utilization of Fintech in Millennial Generation - Bagus Kusuma Wijaya; Made Leo Radhitya; Devi Valentino Waas (Jurnal Scientia, 2023)
This study aims to examine the millennial generation's comprehension and utilization of e-wallets. The questionnaire method was used to acquire data from 28 participants of the millennial generation for this study. Data was collected to determine the extent to which millennials comprehend the concept of e-wallets, their usage frequency, and their preferences for the most desirable features. The results of the analysis indicate that 82.1% of millennials have a deep comprehension of e-wallets and utilize them as an essential tool in their daily financial activities. 94% of respondents have employed e-wallets for online transactions and payment activities. The influence of usability and application features on e-wallet usage preferences. This research can provide valuable insights for e-wallet service providers, businesses, and the government regarding the millennial generation's use of e-wallets. The implications of this study's findings can be used to enhance e-wallet innovation and services, as well as to devise more effective marketing strategies to overcome obstacles and optimize the use of this financial technology.